High sphericity micro-nano silver powder and preparation method thereof
By using sodium borohydride and ascorbic acid as reducing agents, combined with the synergistic effect of polyvinylpyrrolidone and the regulation of sodium hydroxide, high spherical micro-nano silver powder was prepared, solving the problems of complex process and difficult to control particle size in the prior art, and achieving stable and efficient silver powder preparation and large-scale production.
Patent Information
- Application Number
- CN202411654863.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art has cumbersome processes in the preparation of spherical silver powder, the raw materials may be toxic or dangerous, and it is difficult to control particle size and morphology, which affects the batch stability of the product and the difficulty of large-scale production.
Sodium borohydride and ascorbic acid are used as reducing agents to prepare high spherical micro-nano silver powder through the synergistic action of polyvinylpyrrolidone, and sodium hydroxide is used to adjust the pH value and hydrolyze polyvinylpyrrolidone to achieve pseudo-aggregation and rapid settlement of silver ions.
It has achieved the preparation of micro-nano silver powder with high spherical shape and uniform particle size. It has a short process and is non-toxic and pollution-free raw materials. It is suitable for solar photovoltaics and electronic devices, improving batch stability and feasibility of large-scale production.
Smart Images

Figure CN119140840B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal powder preparation, and in particular to a high-sphericity micro-nano silver powder and a preparation method thereof. Background Art
[0002] In recent years, the solar energy industry and the electronics industry have shown a rapid development trend. In these two industries, micro-nano silver powder has been widely used due to its excellent conductive properties, especially in key fields such as solar photovoltaics, electronic devices and sensors, and has become one of the hot research materials. Studies have shown that the performance of micro-nano silver powder and its performance in practical applications are closely related to multiple factors, including the surface morphology, powder size, particle size distribution and dispersibility of silver powder. These factors play a vital role in whether micro-nano silver powder can give full play to its advantages and meet the application needs of different fields.
[0003] Spherical silver powder has a regular shape and a relatively smooth surface, which is conducive to the transmission of electrons. Therefore, in electronic circuits, using spherical silver powder as a conductive filler can reduce losses during signal transmission and improve the working efficiency and stability of the circuit.
[0004] However, there are still some technical difficulties in the preparation of spherical silver powder in the prior art: first, some preparation processes are cumbersome and complicated, and some raw materials may be toxic or dangerous, which not only poses a threat to the health and safety of operators, but also increases the safety risks and environmental pressures in the production process. In addition, a lot of reagents will remain on the surface of the silver powder finally prepared, which is difficult to clean; second, the preparation of spherical silver powder has high requirements for the process. Due to the inability to accurately control some factors and conditions, different batches of spherical silver powder prepared have differences in particle size, morphology, dispersibility, etc., which affects the batch stability of the product and also increases the difficulty of large-scale production; third, in electronic devices, spherical silver powder of a specific particle size is often required to achieve specific performance requirements. However, there are currently few preparation processes that can achieve stable and accurate regulation of the particle size of spherical silver powder.
[0005] In view of this, it is necessary to design a high-sphericity micro-nano silver powder and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a high-sphericity micro-nano silver powder and a preparation method thereof, firstly, using sodium borohydride with stronger reducing property to prepare nano silver crystal nuclei with higher sphericity, then through the synergistic effect of dispersant polyvinyl pyrrolidone and reducing agent ascorbic acid to prepare silver powder with high sphericity and uniform particle size, then using the strong reactivity of sodium hydroxide and polyvinyl pyrrolidone to rapidly hydrolyze polyvinyl pyrrolidone, pseudo-agglomeration occurs between silver ions, and rapid sedimentation occurs, and finally the supernatant is removed to obtain high-sphericity micro-nano Silver powder; the preparation method provided in the present application can adjust the mass of the silver nitrate solid added in step S1 and the mass of the sodium borohydride to adjust the particle size of the high sphericity micro-nano silver powder obtained in step S4, and the particle size of the finally prepared high sphericity micro-nano silver powder is between 50-600nm, which is suitable for the field of solar photovoltaic positive electrode silver paste and electronic paste; the raw materials used in the present application are non-toxic, pollution-free, environmentally friendly, and the process flow is short, the base liquid can be prepared and used immediately, there is no need to prepare crystal nuclei in advance, the batch stability is high, and kilogram-level scale-up production has been achieved.
[0007] In a first aspect, the present invention provides a method for preparing micro-nano silver powder with high sphericity, comprising the following steps:
[0008] S1, dissolving a dispersant in deionized water under stirring, adding solid silver nitrate, and after fully dissolving, first adding a first reducing agent, continuing stirring for 2-5 minutes, and then adding a second reducing agent, stirring until completely dissolved, to obtain a base liquid containing nanosilver crystal nuclei; specifically, the dispersant is polyvinyl pyrrolidone, the first reducing agent is sodium borohydride, and the second reducing agent is ascorbic acid;
[0009] S2, respectively preparing a silver nitrate solution, a third reducing agent solution and a sodium hydroxide solution;
[0010] S3, under stirring conditions, using a peristaltic pump to simultaneously and rapidly drop the silver nitrate solution and the third reducing agent solution into the base solution prepared in step S1, and continue stirring the reaction for 5-10 minutes to obtain a mixed solution;
[0011] S4, adjusting the pH value of the mixed solution in step S3 to 6.5-8 with the sodium hydroxide solution prepared in step S2, stirring sufficiently, standing and settling, then removing the supernatant, collecting the settled silver powder, washing and drying the silver powder to obtain micro-nano silver powder with high sphericity.
[0012] In some embodiments, in step S2, the concentration of the third reducing agent solution is 200-220 g / L, and the third reducing agent solution is ascorbic acid solution.
[0013] In some embodiments, in step S1, the mass ratio of the silver nitrate solid to the sodium borohydride is 1:(0.5-1), and the concentration of silver in the base solution is 0.01-0.02 g / L.
[0014] In some embodiments, the mass ratio of silver nitrate in the silver nitrate solution of step S2 to the polyvinyl pyrrolidone in step S1 is 1:(0.05-0.2); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in step S1 is 1:(0.02-0.05); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in the ascorbic acid solution of step S2 is 1:(0.5-0.8).
[0015] In some embodiments, in step S2, the concentration of the silver nitrate solution is 100-400 g / L, and the concentration of the sodium hydroxide solution is 4-6 mol / L.
[0016] In some embodiments, in step S3, the dropping speeds of the silver nitrate solution and the ascorbic acid solution are both 150-200 mL / min.
[0017] In some embodiments, the mass of silver nitrate solid and sodium borohydride added to the base solution in step S1 is negatively correlated with the particle size of the high sphericity micro-nano silver powder obtained in step S4, that is, as the mass of silver nitrate solid and sodium borohydride added to the base solution increases simultaneously, the particle size of the high sphericity micro-nano silver powder decreases.
[0018] In some embodiments, in step S4, the pH value of the mixed solution is adjusted to 6.5-8 with the sodium hydroxide solution, and after being fully stirred for 5-10 minutes, it is allowed to settle for 1-5 minutes.
[0019] In some embodiments, the washing in step S4 is specifically washing with deionized water first and then washing with ethanol.
[0020] In a second aspect, an embodiment of the present application provides a high-sphericity micro-nano silver powder, which is prepared according to any one of the aforementioned technical solutions, and has a particle size of 50-600 nm.
[0021] The beneficial effects of this application are:
[0022] The present application provides a high-sphericity micro-nano silver powder and a preparation method thereof. First, sodium borohydride with stronger reducing property is used to prepare nano silver crystal nuclei with higher sphericity, and then silver powder with high sphericity and uniform particle size is prepared through the synergistic effect of dispersant polyvinyl pyrrolidone and reducing agent ascorbic acid. Then, the strong reactivity of sodium hydroxide and polyvinyl pyrrolidone is used to rapidly hydrolyze polyvinyl pyrrolidone, pseudo-agglomeration occurs between silver ions, and the silver ions are rapidly precipitated. Finally, the supernatant is removed to obtain high-sphericity micro-nano silver powder. The particle size of the silver powder is between 50-600nm, and the silver powder is suitable for the field of solar photovoltaic positive electrode silver paste and electronic paste.
[0023] First, the present application uses polyvinyl pyrrolidone, silver nitrate, sodium borohydride and ascorbic acid to prepare the base solution in step S1, which not only makes the prepared silver powder more spherical and the particle size more uniform, but also improves the stability of the process, and this base solution can be used immediately without being prepared in advance. The reducing property of sodium borohydride is stronger than that of ascorbic acid. Sodium borohydride is added first, and silver nitrate can be quickly reduced to silver element by sodium borohydride, making the generated nano silver crystal nucleus more round. Since the silver concentration in the system is low at this time, under the action of the dispersant polyvinyl pyrrolidone, the silver element is uniformly and stably dispersed in the solution in the form of nano-scale silver crystal nuclei, while ascorbic acid has weak reducing property and low reaction rate, and is used to participate in the reduction reaction in step S3, which is conducive to further improving the sphericity of the silver powder.
[0024] Secondly, the method of simultaneously adding the silver nitrate solution and the ascorbic acid solution to the base solution in step S3 of the present application is designed according to the composition of the base solution. The entire reaction process of ascorbic acid reducing silver nitrate is relatively fast and belongs to an instantaneous reduction process. When the base solution contains crystal nuclei and ascorbic acid, the concentration of ascorbic acid in the base solution increases rapidly during the process of simultaneously adding silver nitrate solution and ascorbic acid solution. A large amount of elemental silver is reduced in the solution in a short period of time, and the silver element begins to grow on the surface of the crystal nucleus, and finally the crystal nucleus grows into spherical silver powder. When there is no second reducing agent in the base solution, the concentration of ascorbic acid in the base solution is relatively low during the process of simultaneously adding silver nitrate solution and ascorbic acid solution. Moreover, due to the relatively weak reducing property of ascorbic acid, although most of the silver nitrate is reduced to elemental silver and grows on the surface of the crystal nucleus, a small amount of silver nitrate is directly grown into irregular flaky silver powder before it has time to grow on the crystal nucleus after being reduced to elemental silver, and finally the prepared silver powder has a mixed morphology of irregular flaky and quasi-spherical, rather than a uniform spherical morphology.
[0025] Third, the technical effect of the present application cannot be achieved by using other dispersants (non-polyvinyl pyrrolidone). This is because the type of dispersant has a great influence on the morphology of the silver powder, and the performance and addition method of the reducing agent also have a great influence on the morphology of the silver powder. Only by using polyvinyl pyrrolidone as a dispersant and ascorbic acid as a reducing agent, the synergistic effect of the two can the micro-nano silver powder with high sphericity, smooth surface and high crystallinity provided by the present application be produced.
[0026] Fourthly, the present application uses sodium hydroxide to adjust the pH value of the mixed solution after the reaction in step S4, which can, on the one hand, keep the morphology of the silver powder stable and prevent irreversible deformation and agglomeration in an acidic environment; on the other hand, sodium hydroxide can quickly hydrolyze polyvinylpyrrolidone, thereby causing pseudo-agglomeration of the silver powder and rapid flocculation and sedimentation, which is beneficial to shorten the preparation time, and after the polyvinylpyrrolidone is hydrolyzed, the silver powder is easier to clean, and the residual organic matter on the surface is less than 0.2%. The pseudo-agglomeration can be opened by air grinding after the silver powder is dried, and will not affect the morphology of the silver powder.
[0027] In summary, the present application rationally designs a technical solution, fully utilizes the properties of polyvinyl pyrrolidone, sodium borohydride, ascorbic acid and sodium hydroxide, and makes the reagents cooperate with each other to achieve the preparation of spherical silver powder and particle size regulation; the raw materials used are non-toxic, pollution-free, and environmentally friendly, the process flow is short, the base liquid can be prepared and used immediately, there is no need to prepare crystal nuclei in advance, the batch stability is high, and kilogram-level scale-up production has been achieved, which has achieved significant technical progress.
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 1;
[0031] Figure 2 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 2;
[0032] Figure 3 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 3;
[0033] Figure 4 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 4;
[0034] Figure 5 This is the SEM image of the micro-nano silver powder just prepared in Comparative Example 1;
[0035] Figure 6 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 1 after being left for one day;
[0036] Figure 7 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 2;
[0037] Figure 8 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 3;
[0038] Fig. 9 This is the SEM picture of the micro-nano silver powder just prepared in Comparative Example 4;
[0039] Fig.10 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 4 after being left for one day;
[0040] Fig.11 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 5;
[0041] Fig.12 The sedimentation state of silver powder within 2 minutes after adding sodium hydroxide. DETAILED DESCRIPTION
[0042] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0045] In the description of the embodiments of the present application, the term "and / or" is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0046] In the prior art, there are some technical difficulties in preparing spherical silver powder: first, some preparation processes are cumbersome and complicated, and some raw materials may be toxic or dangerous, which not only poses a threat to the health and safety of operators, but also increases the safety risks and environmental pressures in the production process. In addition, a lot of reagents will remain on the surface of the silver powder finally prepared, which is difficult to clean; second, the preparation of spherical silver powder has high requirements for the process. Due to the inability to accurately control some factors and conditions, different batches of spherical silver powder prepared have differences in particle size, morphology, dispersibility, etc., which affects the batch stability of the product and also increases the difficulty of large-scale production; third, in electronic devices, spherical silver powder of a specific particle size is often required to achieve specific performance requirements. However, there are currently few preparation processes that can achieve stable and accurate regulation of the particle size of spherical silver powder.
[0047] The present application provides a high-sphericity micro-nano silver powder and a preparation method thereof. First, sodium borohydride with stronger reducing property is used to prepare nano silver crystal nuclei with higher sphericity, and then silver powder with high sphericity and uniform particle size is prepared through the synergistic effect of dispersant polyvinyl pyrrolidone and reducing agent ascorbic acid. Then, the strong reactivity of sodium hydroxide and polyvinyl pyrrolidone is used to rapidly hydrolyze polyvinyl pyrrolidone, so that pseudo-agglomeration occurs between silver ions and silver ions are rapidly precipitated. Finally, the supernatant is removed to obtain the high-sphericity micro-nano silver powder. The preparation method provided by the present application can adjust the particle size of the high-sphericity micro-nano silver powder obtained in step S4 by adjusting the mass of the silver nitrate solid added in step S1 and the mass of sodium borohydride, so that the particle size of the high-sphericity micro-nano silver powder finally prepared is between 50-600nm. The raw materials used in the present application are non-toxic, pollution-free, and environmentally friendly, and the process flow is short. The base liquid can be prepared and used immediately, and there is no need to prepare crystal nuclei in advance. The batch stability is high, and kilogram-level scale-up production has been achieved.
[0048] In a first aspect, the present invention provides a method for preparing a micro-nano silver powder with high sphericity, comprising the following steps:
[0049] S1, under stirring conditions, dissolve the dispersant in deionized water, add solid silver nitrate, wait until fully dissolved, first add the first reducing agent, continue stirring for 2-5 minutes, then add the second reducing agent, stir until completely dissolved, and obtain a base solution. The dispersant is polyvinyl pyrrolidone, the first reducing agent is sodium borohydride, and the second reducing agent is ascorbic acid.
[0050] Furthermore, in step S1, the mass ratio of silver nitrate solid to sodium borohydride is 1:(0.5-1), and the concentration of silver in the base solution is 0.01-0.02 g / L.
[0051] Sodium borohydride has a stronger reducing property than ascorbic acid. Sodium borohydride is added first, and silver nitrate can be quickly reduced to silver element by sodium borohydride. Since the silver concentration in the system is low at this time, under the action of the dispersant polyvinyl pyrrolidone, the silver element is evenly and stably dispersed in the solution in the form of nano-scale silver crystal nuclei, while ascorbic acid has a weaker reducing property and a lower reaction rate, which is conducive to improving the sphericity of silver powder. The base liquid in this application does not need to be prepared in advance, and it can be used immediately after preparation, which effectively shortens the process flow and time.
[0052] S2, using deionized water as solvent, respectively preparing a silver nitrate solution, a third reducing agent solution and a sodium hydroxide solution. The concentration of the silver nitrate solution is 100-400 g / L, the concentration of the third reducing agent solution is 200-220 g / L, and the concentration of the sodium hydroxide solution is 4-6 mol / L. The third reducing agent solution is an ascorbic acid solution.
[0053] Furthermore, the mass ratio of silver nitrate in the silver nitrate solution of step S2 to the dispersant in step S1 is 1:(0.1-0.2); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in step S1 is 1:(0.02-0.05); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in the ascorbic acid solution of step S2 is 1:(0.5-0.8).
[0054] S3, under stirring conditions, using a peristaltic pump to simultaneously and rapidly drop the silver nitrate solution and the third reducing agent solution into the base solution prepared in step S1, and continue stirring the reaction for 5-10 minutes to obtain a mixed solution.
[0055] Further, in step S3, the dropping speed of the silver nitrate solution and the third reducing agent solution is 150-200 mL / min. In the scale-up test, the dropping speed of the silver nitrate solution and the third reducing agent solution is 1500-2000 mL / min.
[0056] S4, adjusting the pH value of the mixed solution in step S3 to 6.5-8 with the sodium hydroxide solution prepared in step S2, stirring for 5-10 minutes, standing for 1-5 minutes, then removing the supernatant, collecting the settled silver powder, and washing the silver powder with deionized water until the conductivity of the silver powder is less than 20S·m -1 , washed with ethanol, and then dried to obtain high sphericity micro-nano silver powder.
[0057] After the reaction is completed, the pH value of the solution is adjusted with sodium hydroxide solution. On the one hand, the polyvinyl pyrrolidone attached to the surface of the silver powder is hydrolyzed by strong alkali, so that the silver nitrate is rapidly flocculated and precipitated. The supernatant after precipitation is clear and transparent and can be directly removed by suction filtration, which greatly reduces the difficulty of solid-liquid separation. In addition, due to the large amount of hydrolysis of polyvinyl pyrrolidone, the difficulty of subsequent cleaning is also greatly reduced. On the other hand, a large amount of nitric acid (the pH value in the system is between 0.2-0.4) will be generated during the reduction of silver nitrate, making the surface of the silver powder more acidic. The strong acidic environment can easily cause the silver powder to oxidize and turn black, and also easily make the silver powder morphology unstable, resulting in deformation and agglomeration during the washing process. Rapidly adjusting the pH to 6.5-8 with sodium hydroxide solution can keep the silver powder morphology stable during the post-treatment process, so that the final silver powder has a higher sphericity.
[0058] Furthermore, the mass of the silver nitrate solid and the sodium borohydride added to the base solution in step S1 is negatively correlated with the particle size of the high sphericity micro-nano silver powder obtained in step S4, that is, when the mass of the silver nitrate solid and the sodium borohydride added to the base solution is increased at the same time, the particle size of the high sphericity micro-nano silver powder decreases. By adjusting the mass of the silver nitrate solid and the mass of the sodium borohydride added in step S1, the particle size of the high sphericity micro-nano silver powder obtained in step S4 can be adjusted.
[0059] Furthermore, the high sphericity micro-nano silver powder provided in the present application can be prepared at 25-30° C. without heating.
[0060] In a second aspect, the present application further provides a high-sphericity micro-nano silver powder, which is prepared by the preparation method described in any of the aforementioned technical solutions, and has a particle size of 50-600nm.
[0061] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0062] Example 1
[0063] Embodiment 1 provides a method for preparing micro-nano silver powder with high sphericity, comprising the following steps:
[0064] S1. Under stirring conditions, dissolve 6 g of polyvinyl pyrrolidone in 600 mL of deionized water, add 0.0085 g of silver nitrate, stir thoroughly to dissolve, add 0.005 g of sodium borohydride, continue stirring for 3 min, then add 2 g of ascorbic acid and stir until completely dissolved to obtain a base solution.
[0065] S2, prepare silver nitrate solution, third reducing agent solution and sodium hydroxide solution respectively.
[0066] Prepare silver nitrate solution: dissolve 70 g of silver nitrate in 200 mL of deionized water;
[0067] Prepare the third reducing agent solution: dissolve 40 g of ascorbic acid in 190 mL of deionized water;
[0068] Prepare sodium hydroxide solution: dissolve sodium hydroxide in deionized water to a concentration of 4 mol / L.
[0069] S3, under stirring conditions, using a peristaltic pump to simultaneously and rapidly add the silver nitrate solution and the third reducing agent solution to the base solution prepared in step S1, the dropping speed of both is 150 mL / min, and the stirring reaction is continued for 5 minutes to obtain a mixed solution.
[0070] S4, adjusting the pH value of the mixed solution in step S3 to 6.8 with sodium hydroxide solution, stirring for 5 minutes, standing for 2 minutes, and after the silver powder is completely precipitated, removing the supernatant, collecting the precipitated silver powder, first washing it with deionized water, then washing it with ethanol, and then drying it to obtain high sphericity micro-nano silver powder.
[0071] The high sphericity micro-nano silver powder prepared in Example 1 was subjected to TGA test, and the residual organic matter on its surface was 0.12%.
[0072] See also Figure 1 , which is a SEM image of the high sphericity micro-nano silver powder prepared in Example 1. According to measurement, the particle size of the silver powder is between 200-400 nm.
[0073] Example 2-3
[0074] The difference between Example 2-3 and Example 1 is that the amount of silver nitrate solid and sodium borohydride added in step S1 is changed, wherein the amount of silver nitrate solid added is 0.01g (Example 2) and 0.007g (Example 3), and the amount of sodium borohydride added is 0.006g (Example 2) and 0.004g (Example 3), respectively. The other contents are substantially the same as those in Example 1 and will not be repeated here.
[0075] The high sphericity micro-nano silver powder prepared in Examples 2-3 was subjected to TGA test. The residual organic matter on the surface of the high sphericity micro-nano silver powder prepared in Example 1 was 0.14%, and the residual organic matter on the surface of the high sphericity micro-nano silver powder prepared in Example 2 was 0.16%.
[0076] See also Figures 2 to 3 As shown, Figure 2 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 2. According to measurement, the particle size of the silver powder is between 50-200 nm; Figure 3 This is a SEM image of the high sphericity micro-nano silver powder prepared in Example 3. According to measurement, the particle size of the silver powder is between 300-500nm.
[0077] Example 4
[0078] Example 4 provides an amplified test of a method for preparing micro-nano silver powder with high sphericity, comprising the following steps:
[0079] S1. Under stirring conditions, dissolve 600 g of polyvinyl pyrrolidone in 70 L of deionized water, add 0.5 g of silver nitrate, stir thoroughly to dissolve, add 0.3 g of sodium borohydride, continue stirring for 3 min, then add 150 g of ascorbic acid and stir until completely dissolved to obtain a base solution.
[0080] S2, prepare silver nitrate solution, third reducing agent solution and sodium hydroxide solution respectively.
[0081] Prepare silver nitrate solution: dissolve 5 kg of silver nitrate in 15 L of deionized water;
[0082] Prepare the third reducing agent solution: dissolve 2.86 kg of ascorbic acid in 14 L of deionized water;
[0083] Prepare sodium hydroxide solution: dissolve sodium hydroxide in deionized water to a concentration of 4 mol / L.
[0084] S3, under stirring conditions, using a peristaltic pump to simultaneously and rapidly add the silver nitrate solution and the third reducing agent solution to the base solution prepared in step S1, the dropping speed is 1500 mL / min, and the stirring reaction is continued for 10 minutes to obtain a mixed solution.
[0085] S4, adjusting the pH value of the mixed solution in step S3 to 6.8 with sodium hydroxide solution, stirring for 10 minutes, standing for 5 minutes, and after the silver powder is completely precipitated, removing the supernatant, collecting the precipitated silver powder, first washing it with deionized water, then washing it with ethanol, and then drying it to obtain high sphericity micro-nano silver powder.
[0086] The high sphericity micro-nano silver powder prepared in Example 4 was subjected to TGA test, and the residual organic matter on its surface was 0.15%.
[0087] See also Figure 4 , which is a SEM image of the high sphericity micro-nano silver powder prepared in Example 4. According to measurement, the particle size of the silver powder is between 300-500nm.
[0088] Comparative Example 1
[0089] The difference between Comparative Example 1 and Example 1 is that the pH is not adjusted in step S4 (ie, sodium hydroxide is not added), and the other contents are substantially the same as those in Example 1 and will not be described herein.
[0090] The silver powder prepared in Comparative Example 1 was subjected to TGA test, and the residual organic matter on its surface was 0.16%.
[0091] See also Figure 5 to Figure 6 As shown, Figure 5 This is a SEM picture of the micro-nano silver powder just prepared in Comparative Example 1, and the particle size of the silver powder is between 200-400nm. Figure 6 This is a SEM image of the micro-nano silver powder prepared in Comparative Example 1 after being placed for one day. It can be seen that the silver powder just prepared has high sphericity, good dispersibility, and relatively uniform particles, but the morphology of the silver powder changes after being placed for one day, the sphericity becomes lower, and the silver powder particles agglomerate and lose their original morphology. This is because a large amount of nitric acid (HNO3) is produced during the process of silver nitrate being reduced to silver element by ascorbic acid, making the solution after the reaction more acidic, with a pH value of about 0.2, and silver powder is prone to deformation in a strong acidic environment, and this deformation cannot be restored.
[0092] In step S4 of comparative example 1, the silver powder needs to be left to stand for 30-40 minutes for natural sedimentation, which is much longer than the sedimentation time in example 1. This is because adding sodium hydroxide to the mixed solution after the reaction can not only adjust the pH value of the solution to maintain the stability of the silver powder morphology, but also play a flocculation role, so that the silver powder appears pseudo-agglomeration under stirring conditions, that is, the silver powder is agglomerated from small particles into large particles, and quickly settles after the stirring is stopped. The pseudo-agglomeration can be opened by air grinding after the silver powder is dried, and will not affect the morphology of the silver powder. The agglomeration of the silver powder due to deformation in an acidic environment can no longer be opened.
[0093] Comparative Example 2
[0094] Comparative Example 2 provides a method for preparing silver powder, which is different from Example 1 in that the second reducing agent (ascorbic acid) is not added to the base liquid in step S1, and the remaining steps are consistent with Example 1 and will not be repeated here.
[0095] The silver powder prepared in Comparative Example 2 was subjected to TGA test, and the residual organic matter on its surface was 0.13%.
[0096] See also Figure 7 As shown, it is a SEM picture of the micro-nano silver powder prepared in Comparative Example 2. It can be seen that the silver powder prepared in Comparative Example 2 has a low sphericity and an irregular morphology, with a large number of flaky morphologies. This is because the entire reaction process of ascorbic acid reducing silver nitrate is relatively fast and is an instantaneous reduction process. When the base solution contains crystal nuclei and ascorbic acid, the concentration of ascorbic acid in the base solution increases rapidly during the process of simultaneously adding silver nitrate solution and ascorbic acid solution. A large amount of elemental silver is reduced in the solution in a short period of time, and the silver begins to grow on the surface of the crystal nucleus, eventually causing the crystal nucleus to grow into spherical silver powder. When there is no second reducing agent in the base solution, the concentration of ascorbic acid in the base solution is relatively low during the process of simultaneously adding silver nitrate solution and ascorbic acid solution. Moreover, due to the relatively weak reducing property of ascorbic acid, although most of the silver nitrate is reduced to elemental silver and grows on the surface of the crystal nucleus, a small amount of silver nitrate is directly grown into irregular flaky silver powder before it has time to attach to the crystal nucleus after being reduced to elemental silver. Ultimately, the prepared silver powder has a mixed morphology of irregular flaky and quasi-spherical shapes, rather than a uniform spherical shape.
[0097] Comparative Example 3
[0098] Comparative Example 3 provides a method for preparing silver powder, which differs from Example 1 in that in step S3, the dropping speeds of the silver nitrate solution and the third reducing agent solution are both adjusted to 30 mL / min, and the remaining steps are consistent with Example 1 and are not repeated here.
[0099] The silver powder prepared in Comparative Example 3 was subjected to TGA test, and the residual organic matter on its surface was 0.15%.
[0100] See also Figure 8 As shown, it is a SEM image of the micro-nano silver powder prepared in Comparative Example 3. It can be seen that the silver powder prepared in Comparative Example 3 has a low sphericity, a large number of flake morphologies exist, and the morphology is irregular. The reason is similar to that in Comparative Example 3, that is, the silver nitrate solution and the ascorbic acid solution are not evenly mixed with the crystal nuclei in the base solution in the first time, the ascorbic acid concentration in the solution is low, the reaction process is slow, and part of the silver ions are reduced to elemental silver by ascorbic acid, which directly grows into irregular flaky silver powder before it has time to attach to the crystal nuclei, and finally the prepared silver powder has a mixed morphology of irregular flake morphology and spherical-like morphology.
[0101] Comparative Example 4
[0102] The difference between Comparative Example 4 and Example 1 is that in step S4, sodium hydroxide is used to adjust the pH to 4.5, and the other contents are substantially the same as those in Example 1 and will not be repeated here.
[0103] In step S4, when the pH is adjusted to 4.5, the solution becomes a dark yellow suspension, indicating that polyvinylpyrrolidone will be hydrolyzed even when it encounters sodium hydroxide under acidic conditions, and the silver powder will be pseudo-agglomerated and precipitated. The silver powder prepared in Comparative Example 4 was tested by TGA, and the residual organic matter on its surface was 0.18%. It further illustrates that polyvinylpyrrolidone has been hydrolyzed by sodium hydroxide in an acidic environment, making the silver powder easier to wash and having less residual organic matter on the surface. In addition, the high sphericity micro-nano silver powder provided in the present application is easier to wash and is also related to its regular morphology and uniform particle size.
[0104] See also Figures 9 and 10 As shown, Fig. 9 This is the SEM picture of the micro-nano silver powder just prepared in Comparative Example 4. Fig.10 This is the SEM image of the micro-nano silver powder prepared in Comparative Example 4 after being placed for one day. It can be seen that, similar to the situation in Comparative Example 1, the silver powder just prepared in Comparative Example 4 has high sphericity, good dispersibility, and relatively uniform particles, but the morphology of the silver powder has also changed after being placed for one day, the sphericity has become lower, and the silver powder particles have agglomerated and lost their original morphology. This is because the acidity in the solution is still strong when pH=4-5, which still makes the morphology of the silver powder unstable and agglomerates.
[0105] Comparative Example 5
[0106] The difference between Comparative Example 5 and Example 1 is that the dispersant polyvinylpyrrolidone in step S1 is replaced with gum arabic, and the remaining steps are consistent with Example 1 and are not repeated here.
[0107] The silver powder prepared in Comparative Example 5 was subjected to TGA test, and the residual organic matter on its surface was 0.25%.
[0108] See also Fig.11 As shown, it is a SEM image of the micro-nano silver powder prepared in Comparative Example 5. It can be seen that the surface of the silver powder prepared with gum arabic as a dispersant is not smooth, but wooly, and the particle size distribution is wide. This is because the molecular weight of gum arabic is larger than that of polyvinyl pyrrolidone, so the steric hindrance it produces is greater, resulting in a large particle size and a wide particle size distribution of the prepared silver powder, and the morphology of the silver powder is different from that of the silver powder prepared with polyvinyl pyrrolidone. Polyvinyl pyrrolidone (PVP) is a linear structure with polar groups and a polyethylene skeleton in the molecule. The carbon-nitrogen (CN) and carbon-oxygen (C=O) ligands in PVP contribute more to the SP orbital of the silver ion than the hydroxyl group (-OH). Therefore, when PVP is used as a dispersant, the Ag generated in the system + -Silver ions and Ag in PVP complexes +-The silver ions in H2O are more likely to obtain electrons from the reducing agent, which promotes the nucleation of silver ions. Therefore, under the action of ascorbic acid reducing agent, the prepared silver powder has smaller particle size and more uniform size.
[0109] See also Fig.12 As shown, in the preparation method of high sphericity micro-nano silver powder provided by the present application, the sedimentation state of the silver powder within 2 minutes after adding sodium hydroxide in step S4, it can be seen that the silver powder is completely settled at the bottom of the solution, and the supernatant is clear and transparent.
[0110] In summary, the present application provides a method for preparing a high sphericity micro-nano silver powder, firstly using sodium borohydride with stronger reducibility to prepare nano silver nuclei with higher sphericity, then preparing a silver powder with high sphericity and uniform particle size through the synergistic effect of dispersant polyvinyl pyrrolidone and reducing agent ascorbic acid, then using sodium hydroxide and the strong reactivity of polyvinyl pyrrolidone to rapidly hydrolyze polyvinyl pyrrolidone, and pseudo-agglomeration occurs between silver ions, and rapidly settles, and finally removes the supernatant to obtain a high sphericity micro-nano silver powder. The silver powder obtained by the preparation method has a stable morphology, can maintain a high sphericity after being placed for one day, will not agglomerate, and the residual organic matter on the silver powder is very small, only 0.1%-0.2%, and the process stability is high, and the scale production of this type of silver powder has been realized. In addition, the size of the high sphericity micro-nano silver powder finally prepared can be controlled by adjusting the mass of the silver nitrate solid and sodium borohydride added to the base liquid in step S1, and the adjustable range is 50-600nm.
[0111] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing high sphericity micro-nano silver powder, characterized in that: The steps include: S1, dissolving a dispersant in deionized water under stirring, adding solid silver nitrate, and after fully dissolving, first adding a first reducing agent, continuing stirring for 2-5 minutes, and then adding a second reducing agent, stirring until completely dissolved, to obtain a base liquid containing nanosilver crystal nuclei; specifically, the dispersant is polyvinyl pyrrolidone, the first reducing agent is sodium borohydride, and the second reducing agent is ascorbic acid; S2, respectively preparing a silver nitrate solution, a third reducing agent solution and a sodium hydroxide solution; S3, under stirring conditions, using a peristaltic pump to simultaneously and rapidly drop the silver nitrate solution and the third reducing agent solution into the base solution prepared in step S1, and continue stirring the reaction for 5-10 minutes to obtain a mixed solution; S4, adjusting the pH value of the mixed solution in step S3 to 6.5-8 with the sodium hydroxide solution prepared in step S2, stirring sufficiently, standing and settling, then removing the supernatant, collecting the settled silver powder, washing and drying the silver powder to obtain micro-nano silver powder with high sphericity.
2. The method for preparing high sphericity micro-nano silver powder according to claim 1, characterized in that: In step S2, the concentration of the third reducing agent solution is 200-220 g / L, and the third reducing agent solution is ascorbic acid solution.
3. The method for preparing high sphericity micro-nano silver powder according to claim 1, characterized in that: In step S1, the mass ratio of the silver nitrate solid to the sodium borohydride is 1:(0.5-1), and the concentration of silver in the base solution is 0.01-0.02 g / L.
4. The method for preparing high sphericity micro-nano silver powder according to claim 2, characterized in that: The mass ratio of silver nitrate in the silver nitrate solution of step S2 to the polyvinyl pyrrolidone in step S1 is 1:(0.05-0.2); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in step S1 is 1:(0.02-0.05); the mass ratio of silver nitrate in the silver nitrate solution of step S2 to ascorbic acid in the ascorbic acid solution of step S2 is 1:(0.5-0.8).
5. The method for preparing high sphericity micro-nano silver powder according to claim 4, characterized in that: In step S2, the concentration of the silver nitrate solution is 100-400 g / L, and the concentration of the sodium hydroxide solution is 4-6 mol / L.
6. The method for preparing high sphericity micro-nano silver powder according to claim 2, characterized in that: In step S3, the dropping speeds of the silver nitrate solution and the ascorbic acid solution are both 150-200 mL / min.
7. The method for preparing high sphericity micro-nano silver powder according to claim 1, characterized in that: The mass of silver nitrate solid and sodium borohydride added to the base solution in step S1 is negatively correlated with the particle size of the high sphericity micro-nano silver powder obtained in step S4, that is, as the mass of silver nitrate solid and sodium borohydride added to the base solution increases simultaneously, the particle size of the high sphericity micro-nano silver powder decreases.
8. The method for preparing high sphericity micro-nano silver powder according to claim 1, characterized in that: In step S4, the pH value of the mixed solution is adjusted to 6.5-8 with the sodium hydroxide solution, and after being fully stirred for 5-10 minutes, the mixed solution is allowed to settle for 1-5 minutes.
9. The method for preparing high sphericity micro-nano silver powder according to claim 8, characterized in that: The washing in step S4 is specifically washing with deionized water first and then with ethanol.
10. A high sphericity micro-nano silver powder, characterized in that: The high-sphericity micro-nano silver powder is prepared according to the method for preparing high-sphericity micro-nano silver powder according to any one of claims 1 to 9, and the particle size of the high-sphericity micro-nano silver powder is between 50 and 600 nm.
Citation Information
Patent Citations
High specific surface area silver powder improving conductivity of solar battery electrode and preparation method
CN106825544A
Liquid nano silver preparation method
CN109465467A
Cited By
High-sphericity-degree and high-compaction silver powder and preparation method thereof
CN120680004A